Hubungan Tingkat Kepuasan Ibu Dengan Frekuensi Antenatal Care (ANC) - Aisyah, Siti (JOURNAL OF HEALTH SCIENCE, 2025)
Maternal Mortality Rate (MMR) is an indicator that is sensitive to the quality and accessibility of health care facilities. Death related to pregnancy is a problem that until now has not been resolved. This can be seen from the high mortality rate related to pregnancy problems, such as the maternal mortality rate (MMR) and infant mortality rate (IMR) in various parts of the world. Research objective: to determine the relationship between the level of maternal satisfaction with the frequency of Antenatal Care (ANC). This study uses an analytical survey quantitative research design using a cross sectional approach where the independent variable is the level of maternal satisfaction and the dependent variable is Antenatal Care (ANC) frequency. The sample of this research used simple random sampling method. The sample of this study amounted to 82 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of bivariate analysis found that there was a relationship between maternal satisfaction and the frequency of antenatal visits (p value = 0.002). The suggestions are expected to be taken into consideration in decision making, can improve the quality of services and especially regarding the frequency of antenatal care (ANC) visits. Keywords: Maternal Satisfaction, Frequency of Antenatal Care (ANC)